Clinical management of swallowing disorders - Murry, Thomas, 1943-; Carrau, Ricardo L.; Chan, Karen M. K. (San Diego, CA : Plural Publishing, Inc., 2022)
This textbook for speech-language pathology programs examines the diagnosis and treatment of swallowing disorders in children and adults. Thoroughly updated, this popular text emphasizes evidence-based practice, multidisciplinary team management, swallowing safety, nutrition, behavioral treatments, and management following surgical options.
Rehabilitative Swallowing Therapy -- Preventive Swallowing Therapy for Head and Neck Cancer Survivors -- Other Swallowing Treatment Methods -- Summary -- Discussion Questions -- Study Questions -- References -- Chapter 8. Nutrition and Diets -- Introduction -- Dietitian and Dysphagia -- Properties of Liquids and Foods -- Oral Nutrition and Dysphagia Diets -- Nonoral Diets -- Malnutrition and Dehydration -- Summary -- Discussion Question -- Study Questions -- References -- Chapter 9. Swallowing in the Aging Population -- Introduction -- Aging Process Related to Swallowing -- Changes in Swallowing
Dementia.
Description based on online resource; title from digital title page (viewed on January 11, 2021).
Master record variable field(s) change: 050, 082
Keywords: Deglutition disorders; Deglutition disorders -- Diagnosis; Deglutition disorders -- Treatment; Deglutition disorders; Electronic books; Electronic books; Handbooks and manuals